Epigenetics of μ-Opioid receptors: Intersection with HIV-1 infection of the Central Nervous System - Regan, Patrick M. (2012)
The abuse of intravenous drugs, such as heroin, has become a major public health concern due to the increased risk of HIV-1 infection. Opioids such as heroin were originally identified and subsequently abused for their analgesic effects. However, many investigations have found additional effects of opioids, including regulation of the immune system. As such, chronic opioid abuse has been shown to promote HIV-1 pathogenesis and facilitate HIV-1-associated neurocognitive dysfunction. Clinical opioids, such as morphine and methadone, as well as illicit opioids, such as heroin, exert their effects primarily through interactions with the μ-opioid receptor (MOR). However, the mechanisms by which opioids enhance neurocognitive dysfunction through MOR-mediated signaling pathways are not completely understood. New findings in the regulation of MOR expression, particularly epigenetic and transcriptional regulation as well as alternative splicing, sheds new insights into possible mechanisms of HIV-1 and opiate synergy. In this review, we identify mechanisms regulating MOR expression and propose novel mechanisms by which opioids and HIV-1 may modulate this regulation. Additionally, we suggest that differential regulation of newly identified MOR isoforms by opioids and HIV-1 has functional consequence in enhancing HIV-1 neurocognitive dysfunction.